Being ignored at work: Understanding how and when spiritual leadership curbs workplace ostracism in the hospitality industry. (October 2020) - Ali, Moazzam; Usman, Muhammad; Pham, Nhat Tan; Agyemang-Mintah, Peter; Akhtar, Naeem
Highlights: Spiritual leadership is negatively associated with workplace ostracism. Job social support mediates the spiritual leadership-workplace ostracism link. Justice orientation moderates the spiritual leadership-workplace ostracism link. Our research is the first study to examine these effects in the hospitality industry. Abstract: Drawing on the conservation of resources theory, the present study theorizes that spiritual leadership is negatively related to workplace ostracism, both directly and indirectly via job social support and that employees' justice orientation moderates the negative relationship between spiritual leadership and workplace ostracism. Based on time-lagged (three waves, two months apart) survey data collected from 252 hospitality employees, our findings reveal that spiritual leadership is negatively associated with workplace ostracism, both directly and indirectly via job social support. We also find that justice orientation strengthens the negative relationship between spiritual leadership and workplace ostracism. These findings not only highlight core theoretical contributions towards the existing literature on spiritual leadership, job social support, justice orientation, and workplace ostracism but also offer useful practical implications for hotel managers concerned about the repercussions of workplace ostracism for employees' and organizations' outcomes.